ANALISIS PENERAPAN TA’ZIR PADA PEMBIAYAAN MURABAHAH DI BPR SYARIAH MADINAH LAMONGAN - Salkan Salkan; Dwi Aprilianto (JES (Jurnal Ekonomi Syariah), 2019)
The process of transferring or distributing the fund to the customers, or what so called as the outlay needs such a definite contract to apply in the process of job capital budgeting. In BPR Syariah Madinah Lamongan, the contract applied is the contract of mura>bah}ah. It means that the selling prize of goods is as the same as its main prize added with the compromised profit.  It is definitely necessary to observe the expediency of the candidates before transaction while deciding to give the outlay using mura>bah}ah contract, in order to avoid such a certain risks that could fatally affect the bank’s financial loss. Some of the risks emerged because of default. It frequently happens since the debitor or customer is careless to pay the obligation on time.It is certainly contradictory to the Islamic law that intensely protects the interest of both the bank and the customer doing the transaction. So that both sides don’t suffer any loss. Those careless customers should get the proper fine or ta’zi>r. Hence, in this research, the application of ta’zi>r toward the job capital outlay using mura>bah}ah contract in BPR Syariah Madinah Lamongan will be thoroughly analysed through descriptive analysis method. The data collection of this qualitative research is conducted by doing interview, observation and documentation. The research findings reveal that the job capital outlay using mura>bah}ah contract in BPR Syariah Madinah Lamongan needs more serious attention and handling. The process is actually not quite fluent, therefore ta’zi>r needs to be implemented. Whereas the nominal amount of ta’zi>r is already in proper with the customer’s loan stated in the contract. There is only a small number of the customers who get dispensation when being late handing the payment. They are the customers who are really incapable to hand the payment or in force majeure condition. The nominal amount of ta’zi>r then distributed to social fund, such as scholarship, road and bridge construction, etc. Keywords: Implementation of ta’zi>r, The outlay of mura>bah}ah